Racism as Public Health Crisis: Assessment and Review of Municipal Declarations and Resolutions Across the United States - Dara D. Mendez; Jewel Scott; Linda Adodoadji; Christina Toval; Monica McNeil; Mahima Sindhu (Frontiers Media S.A., 2021)
Racism in the United States has been cited as a key driver of racial health inequities. Racism as a public health crisis has been in the forefront, particularly with respect to state and municipal governments that have developed legislation, resolutions, and declarations. This policy brief includes a review of resolutions and declarations across the US related to Racism as a Public Health Crisis through the end of September 2020. There were 125 resolutions reviewed for content related to the history of racism, reference to racial health equity data, content related to action steps or implementation, and any accompanying funding or resources. We found that the majority of policies name racism as critical in addressing racial inequities in health with limited details about specific actions, funding, or resources.